The black hole masses of extremely luminous radio-WISE selected galaxies - Ferris, Emily; Blain, A. W.; Assef, R. J.; Hatch, N. A.; Kimball, A.; Kim, M.; Sajina, A.; Silva, A.; Stern, D.; Diaz-Santos, T.; Tsai, C.-W.; Wylezalek, Dominika (Monthly notices of the Royal Astronomical Society, 2021)
We present near-IR photometry and spectroscopy of 30 extremely luminous radio and mid-IR-selected galaxies. With bolometric luminosities exceeding ∼1013 $\rm {L_{\odot }}$ and redshifts ranging from z = 0.880 to 2.853, we use Very Large Telescope instruments X-shooter and Infrared Spectrometer and Array Camera to investigate this unique population of galaxies. Broad multicomponent emission lines are detected in 18 galaxies and we measure the near-IR lines $\rm {H\,\rm {\beta }}$, $\rm{[O\,{\small III}]}\, \rm {\lambda }\rm {\lambda }4959,5007$, and $\rm {H\,\rm {\alpha }}$ in 6, 15, and 13 galaxies, respectively, with 10 $\rm {Ly\,\alpha }$ and 5 C iv lines additionally detected in the UVB arm. We use the broad $\rm{[O\,{\small III}]}\, \rm {\lambda }5007$ emission lines as a proxy for the bolometric active galactic nucleus luminosity, and derive lower limits to supermassive black hole masses of 107.9-109.4 M⊙ with expectations of corresponding host masses of 1010.4-1012.0 M⊙. We measure $\rm {\lambda }_{Edd}$ > 1 for eight of these sources at a 2σ significance. Near-IR photometry and SED fitting are used to compare stellar masses directly. We detect both Balmer lines in five galaxies and use these to infer a mean visual extinction of AV = 2.68 mag. Due to non-detections and uncertainties in our ${\rm H}\, \beta$ emission line measurements, we simulate a broad ${\rm H}\, \beta$ line of FWHM = 1480 $\rm {kms^{-1}}$ to estimate extinction for all sources with measured ${\rm H}\, \alpha$ emission. We then use this to infer a mean AV = 3.62 mag, demonstrating the highly obscured nature of these galaxies, with the consequence of increasing our estimates of black hole masses by a 0.5 orders of magnitude in the most extreme and obscured cases.
Gesehen am 25.08.2021